The classification of newspaper headlines in Spanish journalist discourse - Yu. V. Vereshinskaya (Ибероамериканские тетради)
The article reviews the different classifications of the Spanish newspaper headlines that were offered by the Spanish linguists. They consider the headline a component of the mediatext that reproduces completely or partly the elements of the text of the article. These investigations concern such areas of linguistics as media linguistics, pragmalinguistics, functional linguistics, theory of the text.